The impact of busy independent directors on the post-IPO operating performance of Chinese companies - Ya-Wei He; Sunita Lylia Hamdan; Sellywati Mohd Faizal (Cogent Business & Management)
This study explores the impact of busy independent directors on the post-IPO operating performance, focusing on the mediating roles of internal control effectiveness and corporate innovation capability, as well as the moderating effects of CEO duality and media attention. This study is based on a dataset of Chinese IPO firms from 2010 to 2022, and uses a regression model controlling for year and industry fixed effects, with several robustness checks, including propensity score matching and instrumental variable approaches. The findings show that busy independent directors significantly enhance post-IPO performance. This positive impact is more pronounced in firms where the roles of the chairman and general manager are separated and media attention is relatively low. The mechanism analysis indicates that busy independent directors primarily improve firm performance through two channels: enhancing the effectiveness of internal controls and strengthening corporate innovation capabilities. This study provides new insights and empirical evidence to address the decline in the post-IPO performance of Chinese firms. The findings offer important practical implications for regulators refining independent director policies, investors evaluating governance quality, and IPO companies aiming to allocate independent director resources more effectively.